Providing Sustainable Business Skill for Millennial Generation in Pembangunan Jaya Senior High School 2 Sidoarjo - Christina Esti Susanti; Marliana Junaedi; Veronika Rahmawati (MITRA: Jurnal Pemberdayaan Masyarakat, 2020)
Generation Y or millennial generation was born in the 1980s to 2000s and therefore students of Pembangunan Jaya 2 Sidoarjo Senior High School belong to this millennial generation. At school, these millennial students only practice making finished goods without any training on entrepreneurship, which includes managerial skills, entrepreneurial management, and technopreneurship. The skills they have been learning so far have only been production-oriented, rather than entrepreneurial management-oriented. Therefore, the aim of this activity was to provide sustainable entrepreneurial skills (managerial and technopreneurship) to students of Pembangunan Jaya 2 Sidoarjo Senior High School. The method of activity included both theory and practice regarding managerial skills in entrepreneurial management, which covers (1) planning, (2) organizing, (3) implementing, (4) controlling, (5) evaluating, (6) motivating and technopreneurship skills as a synergy process from a strong ability in the mastery of technology as well as a comprehensive understanding of the concept of entrepreneurship. The results of the activity show that managerial skills and understanding of technopreneurship in the process and formation of new businesses that involve technology as a basis can create appropriate strategies and innovations in pursuing entrepreneurship. In the long term, it is expected that managerial skills and understanding of technopreneurship will become one of the factors for national economic development.